2014
DOI: 10.1155/2014/920970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Twisted-Tape Turbulators and Nanofluid on Heat Transfer in a Double Pipe Heat Exchanger

Abstract: Heat transfer and overall heat transfer in a double pipe heat exchanger fitted with twisted-tape elements and titanium dioxide nanofluid were studied experimentally. The inner and outer diameters of the inner tube were 8 and 16 mm, respectively, and cold and hot water were used as working fluids in shell side and tube side. The twisted tapes were made from aluminum sheet with tape thickness (d) of 1 mm, width (W) of 5 mm, and length of 120 cm. Titanium dioxide nanoparticles with a diameter of 30 nm and a volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Recent efforts have tried to enhance heat transfer performance of heat exchangers. The applied methods mostly comprise creation of turbulent flow [2] and use of fins, twisters, and baffles [3][4][5]. An obstacle to heat transfer improvement of heat exchangers is the limited thermal properties of conventional coolants.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have tried to enhance heat transfer performance of heat exchangers. The applied methods mostly comprise creation of turbulent flow [2] and use of fins, twisters, and baffles [3][4][5]. An obstacle to heat transfer improvement of heat exchangers is the limited thermal properties of conventional coolants.…”
Section: Introductionmentioning
confidence: 99%
“…By combining the nanofluid enhancement with inserts, [14] found that using Al 2 O 3 nanoparticles with distilled water and full-length twisted tape gave a superior performance with a noticeable increment in friction loses than plain tube. Reference [15], achieved 20 and 2.5% increase in overall heat transfer coefficient and friction factor, respectively, by using nanofluid with single twisted tape insert in double pipe heat exchanger than that without insert. Reference [16] presented an experimental analysis of the turbulent flow in tube fitted with (single, dual, triple, and quadruple) twisted tapes and nanofluid under turbulent flow conditions.…”
Section: Compound Nanoadditive/twisted Tape Enhanced Heat Transfermentioning
confidence: 99%
“…39,40 In recent years, efforts have been made to enhance heat transfer performance of heat exchangers. The applied methods mostly include creation of turbulent flow, 41,42 use of fins, twisters, and baffles. [43][44][45] An obstacle in heat transfer improvement of heat exchangers is the limited thermal properties of conventional coolants.…”
Section: Inside Heat Exchangersmentioning
confidence: 99%